Euthanasia - Medina, Loreta M. (Opposing viewponts series, 2005)
The debate over euthanasia, including its themes and rhetoric, has evolved throughout history. While during the eighteenth up through the early twentieth centuries, the debate focused on the ideas of mercy killing and easy death, during the latter part of the twentieth century, specifically in the 1960s through the 1980s, euthanasia was pushed forward by such ideas as individual rights, self-determination, and choice in dying.